A global-scale assessment of fish mercury concentrations and the identification of biological hotspots - Buck, David G; Evers, David C; Adams, Evan; DiGangi, Joseph; Beeler, Bjorn; Samánek, Jan; Petrlik, Jindrich; Turnquist, Madeline A; Speranskaya, Olga; Regan, Kevin; Johnson, Sarah (The Science of the total environment, 2019)
We present data on a rapid assessment of fish Hg concentrations from 40 different waterbodies in 26 countries that includes data on 451 fish of 92 species. Significant differences in fish Hg concentrations were observed across fish foraging guilds and in general, higher trophic level fish (i.e., piscivores and carnivores) showed the highest mean total Hg (THg) concentrations. However, elevated THg concentrations observed in a lower trophic level, detrivorous species highlights the importance of understanding Hg concentrations across a wide range of trophic levels, and also characterizing site-specific processes that influence methylmercury (MeHg) bioavailability. A linear mixed effects model was used to evaluate the effects of length, trophic level, sampling location, and taxonomy on THg concentrations. A positive, significant relationship between THg in fish and fish size, trophic level, and latitude of the sampling site was observed. A comparison of Hg concentrations across all sites identifies biological mercury hotspots, as well as sites with reduced Hg concentrations relative to our overall sampling population mean Hg concentration. Results from this study highlight the value of rapid assessments on the availability of methylmercury in the environment using fish as bioindicators and the need for expanded biomonitoring efforts in understudied regions of the world. This study also provides insights for the future design and implementation of large-scale Hg biomonitoring efforts intended to evaluate the effectiveness of future Hg reduction strategies instituted by the Minamata Convention on Mercury.
Keywords: chemické látky znečišťující vodu; Environmental Monitoring; Ecosystem; monitorování životního prostředí; Human health criteria; rtuť; potravní řetězec; Water Pollutants, Chemical; Mercury; Minamata convention; Biomonitoring; Food Chain; ryby; Fishes; Animals; zvířata; ekosystém; Seafood; potrava z moře (živočišná)